CHOP regulates the p53–MDM2 axis and is required for neuronal survival after seizures - Engel, Tobias; Sanz-Rodgriguez, Amaya; Jimenez-Mateos, Eva M.; Concannon, Caoimhin G.; Jimenez-Pacheco, Alba; Moran, Catherine; Mesuret, Guillaume; Petit, Emilie; Delanty, Norman; Farrell, Michael A.; O’Brien, Donncha F.; Prehn, Jochen H. M.; et al. (Brain (London, England : 1878), 2013)
Hippocampal sclerosis is a frequent pathological finding in patients with temporal lobe epilepsy and can be caused by prolonged single or repeated brief seizures. Both DNA damage and endoplasmic reticulum stress have been implicated as underlying molecular mechanisms in seizure-induced brain injury. The CCAAT/enhancer-binding protein homologous protein (CHOP) is a transcriptional regulator induced downstream of DNA damage and endoplasmic reticulum stress, which can promote or inhibit apoptosis according to context. Recent work has proposed inhibition of CHOP as a suitable neuroprotective strategy. Here, we show that transcript and protein levels of CHOP increase in surviving subfields of the hippocampus after prolonged seizures (status epilepticus) in mouse models. CHOP was also elevated in the hippocampus from epileptic mice and patients with pharmacoresistant epilepsy. The hippocampus of CHOP-deficient mice was much more vulnerable to damage in mouse models of status epilepticus. Moreover, compared with wild-type animals, CHOP-deficient mice subject to status epilepticus developed more spontaneous seizures, displayed protracted hippocampal neurodegeneration and a deficit in a hippocampus-dependent object-place recognition task. The absence of CHOP was associated with a supra-maximal induction of p53 after status epilepticus, and inhibition of p53 abolished the cell death-promoting consequences of CHOP deficiency. The protective effect of CHOP could be partly explained by activating transcription of murine double minute 2 that targets p53 for degradation. These data demonstrate that CHOP is required for neuronal survival after seizures and caution against inhibition of CHOP as a neuroprotective strategy where excitotoxicity is an underlying pathomechanism.